The Effect of Organizational Culture and Personality on Organizational Citizenship Behavior Mediated by Organizational Commitment on the Employees of PT Bank Tabungan Negara (Persero) Tbk Jember - Ida Nur Kholisah; Sampeadi Sampeadi; Markus Apriono (e-Journal Ekonomi Bisnis dan Akuntansi, 2020)
This study aims to examine and analyze the effect of organizational culture and personality on organizational citizenship behavior mediated by organizational commitment on the employees of PT. Bank Tabungan Negara (Persero) Tbk Jember. This is a descriptive explanatory research. The population was all employees of PT. Bank Tabungan Negara (Persero) Tbk Jember with the sample consisted of 98 respondents taken by census sampling. Research data were analyzed using path analysis. Results showed that organizational culture and personality have a significant and positive effect on organizational commitment, organizational culture and personality have a significant and positive effect on organizational citizenship behavior, and organizational commitment has a significant and positive effect on organizational citizenship behavior of the employees of PT. Bank Tabungan Negara (Persero) Tbk Jember. These results imply that good organizational culture and personality can improve organizational citizenship behavior, directly, or indirectly as mediated by organizational commitment.